The GroJp Explicit Methods for Parabolic Problems with Cylindrical and Spherical Symmetry - Sahimi, Mohamad Salleh; J.Evans, David (1991)
The group explicit (GE) strategy which has been used success Jully to solve parabolic panial diferential equations in regular domains involving 1 and 2 space dimensions by Evans and Abdullah (1983) is now applied to parabolic problems involving regular domains that possess both cylindrical and spherical symmetry. The results indicate that the GE methods are still applicable possessing many of their previous advantages but with a reduced stability range.